(3GdJfHjg hGdEaUGM YeG hbY aj cJGH GdUMGMs - (3CHh eMeO YHO Gddg Hf HQi Hf YHO GdLHGQ GdebOSis; (3ESeGYjd Hf MeGO GdLhgQj, CHh fUQ,J (B393 (3g` s
(3ChdgG (B:s
(3jHOC HHGH aQUO s
(3BNQgG (B:s
(3jfJgi HHGH hbT s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1072s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHOjQi HGdbOS s
Keywords: (3GddZIs